(untitled) (Journal of Educational Sciences, 2025)
This study examines the professional identity of teachers of English as a Foreign Language (EFL) in the Turkestan region of Kazakhstan. A qualitative research design, including semi-structured interviews, was employed to explore the multifaceted aspects of identity formation in the context of language teaching. MAXQDA 24 software was used for data analysis. The data collected during the interviews were analyzed through thematic analysis. The study highlights the complexities involved in the development of teacher identity, emphasizing the importance of personal experience and teaching methods. The findings provide deeper insight into how English teachers carry out their professional roles. The authors offer valuable implications for improving teacher education and supporting initiatives aimed at fostering a strong sense of professional identity among language teachers. The research addresses the following questions: What key factors and experiences shape the professional identity of English as Foreign Language teachers? How do these factors influence their teaching practices and interactions with students? The study offers an understanding of potential ways to support English teachers on their path to a more resilient and sustainable professional identity, ultimately enhancing teaching practices and student learning outcomes in English language education. Key words: professional identity, in-service teachers, EFL (English as a Foreign language), qualification, professional development.